The electronic document imposes a new mode of file in the public entities (2017)
The documental management is very significant for all the organizations for been an aspect of the public administration which allows keep all the relevant information for the decision-making. The technological development has brought important changes in the politics and archivist practices around the world, that’s why in Colombia were implemented international standards to stablish key aspects and requirements in matter of Electronic Records Management System (ERMS), for that, entities such as Archivo General de la Nación and the Ministerio de las Tecnologias y la Informacion have worked together to achieve the orienteering in this matter for the different entities of the Colombian State in all their levels. Modernization and technification of the documental systems means a higher level of clarity and celerity for the citizens to access the public information which is a constitutional right.